(untitled) (Indian Journal of Public Health Research & Development, 2024)
Background: The covid pandemic in India had put health-care workers (HCW) working in the frontline on the challenging end as they were facing the COVID-19 crisis diligently from the beginning of the pandemic in different positions and calibre. The present study was carried out to evaluate the mental health status of health care workers (HCWs) involved in the management of COVID-19 in Visakhapatnam, Andhra Pradesh. Objective: The objective of this study was to assess the mental health status of the health care workers (HCWs) and quantify the magnitude of Insomnia, anxiety, depression and stress. Methodology: An online cross-sectional study using google forms was conducted among 166 health care workers including doctors and nurses involved in the management of COVID-19 patients at four different covid care centres out of 13 covid care centres in Visakhapatnamselected by random sampling method. Sleep Condition Indicator (SCI), Generalized Anxiety Disorder 7-item (GAD-7), Patient Health Questionnaire-9 (PHQ-9) and Perceived Stress Scale-10 (PSS-10) were used to assess the mental health disorders. Results: Prevalence of Insomnia was noted among 24.10% of the study and anxiety was estimated to be 19.3%. Mild depression was noted in 17.5%, while moderate, moderately severe and severe depression was noted in 11.4%, 6.6% and 2.4% of the study participants respectively. High perceived stress was noted in 3.6%, while 70.5% had moderate stress and 25.9% had low stress among the study participants. Conclusion: These findings emphasize the need to identify health-care workers who were at risk in order to provide them with comprehensive support and coping strategies to deal with them at an early stage during the pandemic situations.